2003
DOI: 10.1071/ar02221
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the n-alkane technique to estimate intake, digestibility, and diet composition in sheep consuming mixed grain:roughage diets

Abstract: The usefulness of the n-alkane technique to estimate intake, digestibility, and diet composition in sheep fed mixed diets was tested in an experiment with 16 ewes consuming 4 different proportions of barley grain and straw ranging from 15:85 to 60:40. Two cases were considered: (1) straw as one component or (2) straw separated into leaves and stems. The relationship between estimated (Y) and observed (X) proportion of grain in the diet was highly significant (1: Y = 0.2355 + 0.9945X, r2 = 0.9999; 2: Y = –2.47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 24 publications
4
36
2
3
Order By: Relevance
“…Recovery of natural alkanes was much lower than that observed in cattle fed temperate grasses Oliván et al, 2007), but similar to that recorded in tropical conditions (Hendricksen et al, 2002). The reasons for such differences may be sought in either animal/breed variability (Hendricksen et al, 2002;Valiente et al, 2003) or in the amount and structure of NDF. In this respect, it must be pointed out that the average concentration of cell wall in our forage was 680 g/g DM, a value well above that found in temperate lucerne hay by Oliván et al (2007) or Keli et al (2008) (472 and 463 g/kg DM, respectively), but below the NDF concentration found by Valiente et al (2003) in barley straw (816 g/kg DM).…”
Section: Resultsmentioning
confidence: 46%
See 4 more Smart Citations
“…Recovery of natural alkanes was much lower than that observed in cattle fed temperate grasses Oliván et al, 2007), but similar to that recorded in tropical conditions (Hendricksen et al, 2002). The reasons for such differences may be sought in either animal/breed variability (Hendricksen et al, 2002;Valiente et al, 2003) or in the amount and structure of NDF. In this respect, it must be pointed out that the average concentration of cell wall in our forage was 680 g/g DM, a value well above that found in temperate lucerne hay by Oliván et al (2007) or Keli et al (2008) (472 and 463 g/kg DM, respectively), but below the NDF concentration found by Valiente et al (2003) in barley straw (816 g/kg DM).…”
Section: Resultsmentioning
confidence: 46%
“…Faecal recovery of natural alkanes increased with chain length, recoveries up to 77.0% (C 35 ), whereas dosed alkanes C 28 , C 32 and C 36 showed average recoveries of 94.2%, 97.2% and 86.8%, respectively. Increasing recovery of n-alkanes with chain length has also been observed by Mayes et al (1986b), Dove et al (2002), Valiente et al (2003) and Keli et al (2008), among others.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations